Research progress of chronic low⁃grade inflammation and sleep disorders - LIU Yin; TANG Yong⁃hong; ZHAI Jin⁃xia; QIU Yuan (Chinese Journal of Contemporary Neurology and Neurosurgery, 2023)
Sleep disorders can lead to persistent immune responses, activate related signal transduction pathways, and keep the body in a low⁃grade inflammatory state, which is a state of the level of proinflammatory factors is increased but does not cause invasive tissue damage or dysfunction. Long⁃term persistent chronic low ⁃ grade inflammation (CLGI) can promote the occurrence and development of sleep disorders. This article reviews the research progress of CLGI and sleep disorders, and explores new targets for the treatment of sleep disorders.